Pengaruh Arus Kas Operasi, Tingkat Hutang Dan Ukuran Perusahaan Terhadap Persistensi Laba Dengan Book Tax Defferences Sebagai Variabel Moderating - Supriono Supriono (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2021)
Financial statements are one source of information about an entity that reflects the financial condition of the results of the company's operations in a certain period. Users of financial statements consider that high profit means the business or company is in good condition, without thinking about how the profit process is obtained and whether the profit is a sustainable profit. Profits in the company are short-term, meaning that they can change over time. This study aims to calculate and analyze the effect of operating cash flow, debt levels, and company size on earnings persistence. In addition, this study also aims to calculate and analyze whether the book tax differences moderate the relationship between each variable operating cash flow, debt level, and company size on earnings persistence. This study uses a sample of companies listed on the Indonesia Stock Exchange for the period 2016 to 2019 for mining sector companies. The number of samples is 32 companies, using purposive sampling technique. The data analysis technique used multiple linear regression analysis and regression analysis of moderating variables with absolute difference method.The results of this study indicate that operating cash flow has a negative and insignificant effect on earnings persistence, firm size has a positive and significant effect on earnings persistence and the level of debt has a positive and significant effect on earnings persistence. The results of this study are related to the moderating variable Book tax differences moderating the effect of operating cash flow on earnings persistence, the tax book differences moderating the relationship between the variable debt level and earnings persistence, the tax book differences variable did not moderate the relationship between firm size and earnings persistence.